ANALISIS PENGGUNAAN METODE BERNYANYI DALAM PEMBELAJARAN UNTUK SIKAP SOSIAL EMOSIONAL SISWA KELAS 1 SDN 2 HADIPOLO - Febriska Marseila; Wawan Shokib Rondli; F. Shoufika Hilyana (STKIP Subang, 2023)
Education for children is the basis for forming children's behavior and attitudes, the learning provided is expected to be able to develop all aspects of their development, especially in the social-emotional aspects of children, because the education given to children determines how the child's future will be in the future. This study aims to determine the use of the singing method for the social and emotional attitudes of the first graders of SD N 2 Hadipolo. Social attitude is a person's awareness to behave in a certain way and in a certain environment towards social objects. This attitude is also not only expressed by oneself but also noticed and expressed by people in their environment. Emotional attitude is every state in a person that is accompanied by an affective color both at a weak (superficial) level and at a broad (deep) level. In this study, researchers will analyze the use of the singing method for social emotional attitudes of grade I SD N 2 Hadipolo students. The singing method is a way to communicate with students so that the learning process in class is more effective, therefore the singing method is very necessary in the teaching and learning process. The approach in this study uses a descriptive qualitative approach. Data collection techniques that researchers use are observation data, interviews, and documentation. Data analysis used in this research is data reduction, data presentation, and conclusion.